CORAK PENAFSIRAN JALÄ€LUDDÄªN AL-SUYÅªá¹¬Äª: STUDI ATAS KITAB TAFSÄªR JALÄ€LAYN - dan Adrika Fithrotul Aini, Syarwani (IAIN Kediri, 2015)
TafsÃ„Â«r JalÃ„Âlayn is one among other exegetical works commonly used in Indonesia, particularly in pesantrens.Ã‚Â It is well-known that this work is relatively concise and straightforward that people can easily understand it.Ã‚Â This paper attempts to discuss the authors of the work with a focus on JalÃ„ÂluddÃ„Â«n al-SuyÃ…Â«Ã¡Â¹ÂÃ„Â« who completed andÃ‚Â continued the work of JalÃ„ÂluddÃ„Â«n al-MaÃ¡Â¸Â¥allÃ„Â«. It will examine al-SuyÃ…Â«Ã¡Â¹ÂÃ„Â«Ã¢â‚¬â„¢s types and methods in his interpretationÃ‚Â work after the latter.Keywords: al-SuyÃ…Â«Ã¡Â¹ÂÃ„Â«, Tafsir al-JalÃ„Âlayn, Tipologi TafsÃ„Â«r